2015
DOI: 10.4018/ijisss.2015010101
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Services Discovery Model for Better Leveraging BPM and SOA Integration

Abstract: This work addresses the problem of BPM-SOA integration using the services discovery activity as the main driver for that. The developed model is able to select the most adequate (web) services for given business transactions that are modeled at BPM level, regarding their business' contexts and QoS restrictions. It considers an inter-organization scenario, where services are published and made available by disparate providers over largely distributed and heterogeneous repositories, which can also be accessed un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…For example, Cancian et al [4] have identified the list of BPs that software service providers have to support in the collaboration life cycle (including services provision and support) considering aspects like partners' and services' certifications, governance and trustworthiness. Perin et al [10] have developed a dynamic services discovery environment that works over disparate UDDI-based services repositories considering BPs' context and QoS to better support BPM-SOA integration. Using different IT supporting approaches, Camarinha-Matos et al [13] and Obidallah [14] have developed platforms to identify and to better link BPs' needs to partners' competences and software services within a CNO.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Cancian et al [4] have identified the list of BPs that software service providers have to support in the collaboration life cycle (including services provision and support) considering aspects like partners' and services' certifications, governance and trustworthiness. Perin et al [10] have developed a dynamic services discovery environment that works over disparate UDDI-based services repositories considering BPs' context and QoS to better support BPM-SOA integration. Using different IT supporting approaches, Camarinha-Matos et al [13] and Obidallah [14] have developed platforms to identify and to better link BPs' needs to partners' competences and software services within a CNO.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the key elements of the catalogue environment is the discovery service [10], developed in the scope of this work. It supports the search, analysis, selection and final binding of the services (from the services federation) that fit best the set of functional and non-functional requirements of the application(s) under construction.…”
Section: The Catalogue's Architecture and Prototypementioning
confidence: 99%
See 1 more Smart Citation